Digital-Based SAK EMKM Training for Improving MSME Accounting and Tax Literacy - Vista Yulianti; Agus Fuadi; Sindik Widati; Ilfah Nur Azizah (Lentera Ilmu Nusantara, 2026)
Micro, Small, and Medium Enterprises face various challenges in financial and tax management, particularly related to limited accounting knowledge, inadequate financial reporting practices, and low utilization of digital technology in recording business transactions. These conditions affect the quality of financial information and limit entrepreneurs' ability to fulfill their tax obligations properly. This community service program aimed to improve accounting and tax literacy among business owners through the implementation of financial reporting practices supported by digital tools. The program was conducted through socialization, training, hands-on practice, and mentoring involving nine micro and small business owners in Bekasi Regency. The training covered basic accounting concepts, financial statement preparation, tax management, and the use of digital tools for transaction recording and financial reporting. The results indicated an improvement in participants' understanding of financial and tax management, enhanced ability to record transactions digitally, and increased competence in preparing systematic and structured financial statements. Participants also demonstrated positive acceptance of digital technology as a supporting tool for business management. This program contributed to strengthening managerial capacity, supporting better business decision-making, improving tax compliance, and promoting more professional and sustainable business governance.